Simulated operation of an enhanced production line counter using proteus professional design suite - Adekanmbi, Martins; Ogotute, Anthony Awajisenyinayenmi; Amaechi, Chukwuwendu Jeffrey (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2024)
An essential part of contemporary industrial optimization is the ability to mimic the functioning of production line counters. This allows manufacturers to test, tweak, and improve the systems' performance before putting them into real-world settings. Focusing on the use of technologies like the Proteus Professional Design Suite, this research investigated the principles, approaches, and advantages of mimicking production line counters. Simulations allow producers to evaluate the effects of different variables on production line performance by integrating pertinent data sources, accurately representing system behaviour, and using dynamic modelling approaches. Saving money, making better decisions, minimizing risks, and optimizing processes are all possible thanks to simulated operations. To keep up with the ever-changing industrial scene, producers may use simulation tools to proactively solve problems, enhance processes, and remain competitive.